(untitled) (Tanzania Medical Journal, 2023)
Background Improvement in the management of children with sickle cell anemia (SCA) has increased their lifespan. This has led to emergence of various endocrinopathies such as diabetes mellitus (DM). Glycosylated hemoglobin (HbA1c) levels have been shown to be low among children with sickle cell anemia (SCA) by various studies. This can lead to under diagnosis of DM in SCA children, hence delaying their treatment. There is a need to establish normal ranges of HbA1c levels among children with SCA attending Muhimbili National Hospital in Dar-e-Salaam, Tanzania. Objectives To determine the reference range of HbA1c levels among children with SCA attending clinics at Muhimbili National Hospital in Dar-es-salaam, Tanzania. Methodology This was a hospital-based cross-sectional study conducted at Pediatric clinics in Muhimbili National Hospital involving children from 9 months to 14 years. 120 children with SCA and 40 children without SCA were recruited. HbA1c levels were reported as median and IQR while hemoglobin levels were reported as mean ± standard deviation. Independent t-test and Mann Whitney test were used for analysis of continuous data. Results The reference range of HbA1c levels in children with SCA was from 3.4% to 5.2%. Median HbA1c level in children with SCA was 4.2% (4.1% - 4.6%) while for children without SCA it was 5.3% (4.9% - 5.5%) with p-value < 0.001. Mean hemoglobin levels were 8.26 (±1.22) g/dl in SCA children compared to 11.55 (± 1.31) g/dl in children without SCA with p-value of < 0.001 Conclusion and Recommendation The reference range of HbA1c levels in children with SCA was from 3.4% to 5.2%. Children with SCA had significantly lower levels of HbA1c compared to children without SCA. Health personnel are advised to use HbA1c reference ranges obtained from this study when screening for diabetes mellitus among children with SCA.